The ability of some local fungal isolates to produce xylanase and studying of the enzymatic activity (Latakia University Journal -Biological Sciences Series, 2022)
The following fungal species were isolated from therhizosphere of olive plant (Olea europaea.L): Trichoderma harzianum, T.viride, T.longibrachiatum and T.asperellum. It was shown that all isolated fungi had capacity to produce xylanase using an agricultural weed, Prosopis juliflora pods were powdered in the grinder and sieved. The particles with size of 0.425 mm pods were used in the study. Trichoderma spp (105 spores/mL) was included into 250 mL erlenmeyer flask containing 100 mL sterilized medium (30 g/L pretreated pods and 4 g/L calcium carbonate) at PH 6.5 and incubated at 30 °C for 120 h in a shaker at 150 rpm, while the fungus Trichoderma harzianum gave the highest capacity for the production of this enzyme (208.4 U/mL). the fungus T.longibrachiatum gave less productive ratio (20.6 U/mL).the study of different carbon sources for the fungus Trichoderma harzianum, T.viride, T.longibrachiatum and T.asperellum showed that sucrose was the best media in xylanase productivity. Also The study of different nitrogen sources for the fungus Trichoderma harzianum, T.viride, T.longibrachiatum and T.asperellum showed that yeast extract was the best media in xylanase productivity for Trichoderma harzianum, T.viride, T.longibrachiatum but casein  was the best media in xylanase productivity for T.asperellum.